Thermochronological evidence of a low‐angle, mid‐crustal detachment plane beneath the central South Island, New Zealand. (28th October 2016) - Warren‐Smith, Emily; Lamb, Simon; Seward, Diane; Smith, Euan; Herman, Frédéric; Stern, Tim
Abstract: Oblique continental convergence and uplift in the Southern Alps, New Zealand is largely accommodated by dextral transpression on the Alpine Fault. However, toward the south of the orogen the Alpine Fault becomes increasingly strike‐slip, despite evidence for high exhumation rates in the Pacific plate. Here we present 41 new apatite and zircon fission‐track ages to investigate the role of the southern Alpine Fault in Pacific plate exhumation since the Miocene. Through development of a new, maximum likelihood fission‐track age calculation method (to overcome extremely low (<0.1 ppm) 238 U concentrations in apatites) we estimate the width of the fully reset apatite zone (ages <5 Ma) southeast of the southern Alpine Fault, which has been previously overestimated. Instead, this zone is ∼30 km wide, rather than 60 km. We combine our exhumation profile with thermo‐kinematic modeling to impose constraints on fault kinematics and deformation history. The surface cooling age pattern can be well reproduced by exhumation along a listric reverse fault, which shallows to a low‐angle (6–10°) mid‐crustal detachment beneath the Southern Lakes. This structure is comparable to the listric central Alpine Fault geometry previously constrained by thermo‐kinematics models to the north of our study region. We propose this detachment plane is continuous beneath a large region of central South Island and may be acting to accommodate underthrusting of Australian crust beneath the Pacific plate. Key Points: We quantify exhumation in the Southern Alps through a new maximum‐likelihood fission‐track age calculation method for low uranium samples The cooling age pattern can be reproduced by exhumation by a listric fault geometry, shallowing to a low‐angle mid‐crustal detachment This detachment may be continuous beneath the central South Island, acting to accommodate underthrusting of Eocene rifted Australian crust